Efisiensi Penggunaan Faktor Produksi Pupuk pada Usahatani Cabai Merah di Desa Lamokuni Kecamatan Wonggeduku Barat Kabupaten Konawe - Kalis Amartani; I Made Sukratman; Anugrah Anugrah; M. Ikram Irwan (Universitas Kristen Indonesia Toraja, 2023)
The purpose of this study was to determine the Level of Efficiency of Fertilizer Production Factor Use in Red Chili Plants in Lamokuni Village, Wonggeduku Barat District, Konawe Regency. The research location is in Lamokuni Village, Wonggeduku Barat District, Konawe Regency. The selection of the research location was carried out intentionally (purposive), with the consideration that Lamokuni Village, Wonggeduku District, Konawe Regency is one of the areas that has very good potential in developing red chili farming. The researcher determined that the entire population of 30 people were made respondents, which is referred to as a census. The analysis of production factor efficiency uses the price efficiency calculation formula based on the use of the Cobb-Douglass production function technique. The use of fertilizer production factors is not efficient for red chili farming in Lamokuni Village, Wonggeduku Barat District, Konawe Regency. This is indicated by the efficiency value which is not equal to one (NPMx ≠ 1), namely; the efficiency value of SP 36 is 0.70, the efficiency value of NPK Ponska is 0.87, the efficiency value of NPK Mutiara is 0.66 and the efficiency value of liquid organic fertilizer is 2.07. This means that the use of fertilizer production factors in the farming business is still very wasteful.